Analisis Perbandingan Kualitas Website Gramedia.com dan BPKGunungMulia.com Menggunakan WebQual 4.0 Berbasis Persepsi Pengguna - Alicya Emmanuel Siahaan; Semlinda Juszandri Bulan; Menhya Snae (Fakultas Teknik Universitas Hamzanwadi, 2026)
This study aims to analyze and compare the quality of the Gramedia.com and BPKGunungMulia.com websites based on user perceptions in the Kupang region using the WebQual 4.0 method. This research was conducted because no comparative study had previously examined both online bookstore websites in the Kupang region. A descriptive quantitative approach was employed using a Likert-scale online questionnaire distributed to 200 respondents, consisting of 100 Gramedia.com users and 100 BPKGunungMulia.com users selected through purposive sampling. Data were analyzed using validity tests, reliability tests, and descriptive statistical analysis with SPSS and Microsoft Excel. The results indicate that both websites are categorized as good. Gramedia.com achieved an average score of 79.31, while BPKGunungMulia.com achieved an average score of 79.23. Gramedia.com performed better in Information Quality (79.63) and Service Interaction Quality (79.07), whereas BPKGunungMulia.com performed better in Usability Quality (79.13) and User Satisfaction (79.87). All research instruments were found to be valid and reliable. These findings provide empirical evidence regarding the quality of online bookstore websites based on user perceptions and may serve as a reference for website managers in improving service quality and user experience.